CODE SWITCHING IN NOVEL ENTITLED “CHINA RICH GIRLFRIEND” BY KEVIN KWAN - Zeannosky Djingga; Roma Ayuni Aminoeddin Loebis; Alemina Perangin-angin (Universitas Negeri Medan, 2021)
Abstract The present paper is a descriptive qualitative research regarding the issue of code switching found in China Rich Girlfriend, a novel by Kevin Kwan. The analysis refers to Poplack‟s (1980) theory that consist three types of code-switching and Gumperz‟s (1982) theory that mentions six functions of code-switching. The result can be concluded as: the dominant types of code-switching by the characters is intra-sentential switching which represents 54 data (46,5%), tag switching is 51 data (44,0%) and inter-sentential switching is 11 data(9,5%). Most dominant functions expressed by the use of code switching found in the novel is interjections which consist 40 data (34,5%), and personalization 34 data (29,3%), addressee specification 19 data (16,3%), message qualification 19 data (16,3%), quotation 2 data (1,8%), and reiteration 2 data (1,8%). Keywords: Code Switching, Sociolinguistics, Novel, Types, Functions